Where have all the voices gone - Tuan, Szi Yi (2017)
Where Have All the Voices Gone explores the history of muses, daemons and inspirations dating back to Classical Greek and Roman times. This pantheon of voices was once considered a gift bestowed upon all people and was often linked to a divine and universal source of creativity. Through a series of maps, info-graphics and a publication, this FYP will share stories and visualize the magical realm of these voices with the hope of inspiring wonder and delight, and possibly even a space for my audience to conjure up their muse.